Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd005436.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Oral zinc for treating diarrhoea in children

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 162 publications
2
50
0
10
Order By: Relevance
“…At 72 and 96 hours, the zinc group had less diarrhea compared to the control group (45% vs. 86%, respectively). A meta-analysis (including 18 clinical trials with 6165 participants) showed that zinc supplementation resulted in a shorter diarrhea duration in acute diarrhea, and less diarrhea at Day 3 and Day 5, similar to our results (17). In contrast to other studies, a recently made double-blind randomized study about zinc supplementation for acute diarrhea in Switzerland showed that zinc treatment decreases the frequency and severity of diarrhea in children aged 2 months to 5 years old, but not the duration of diarrhea (20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At 72 and 96 hours, the zinc group had less diarrhea compared to the control group (45% vs. 86%, respectively). A meta-analysis (including 18 clinical trials with 6165 participants) showed that zinc supplementation resulted in a shorter diarrhea duration in acute diarrhea, and less diarrhea at Day 3 and Day 5, similar to our results (17). In contrast to other studies, a recently made double-blind randomized study about zinc supplementation for acute diarrhea in Switzerland showed that zinc treatment decreases the frequency and severity of diarrhea in children aged 2 months to 5 years old, but not the duration of diarrhea (20).…”
Section: Discussionsupporting
confidence: 90%
“…Zinc deficiency is a major determinant factor of immunity and low weight in developing countries, and both are related with the duration of diarrhea (13)(14)(15). The administration of zinc was shown to reduce the duration of the diarrhea as well as frequency and amount of the stool in randomized controlled trials and reviews (16)(17)(18). The World Health Organization recommends routine use of zinc supplementation, at a dosage of 20 mg per day for children older than six months.…”
Section: Discussionmentioning
confidence: 99%
“…[11] A systematic Cochrane review of 24 trials involving more than 9000 children have suggested that supplementation of zinc in the treatment of diarrhea might reduce the duration of diarrhea in children aged six months or more. [12] …”
Section: Studies Suggesting Role Of Zinc Therapy In Childhood Diarrheamentioning
confidence: 99%
“…A Cochrane review evaluated the efficacy and safety of zinc supplements in the treatment of diarrhoea in children (Lazzerini et al, 2008).…”
Section: Zincmentioning
confidence: 99%